Ventricular fibrillation amplitude spectral area as a guide to deliver the optimal energy level for defibrillation. (3rd October 2022) - Gentile, F R; Compagnoni, S; Baldi, E; Primi, R; Bendotti, S; Currao, A; Aramendi, E; Isasi, I; Contri, E; Palo, A; Savastano, S
Abstract: Introduction: In case of cardiac arrest due to ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT), the optimal energy should be the lowest energy effective to achieve defibrillation minimizing the current-induced myocardial damage. Therefore, it would be ideal to minimize the energy level as well as the number of shocks during resuscitation. ECG-based VF waveform analysis features such as amplitude spectral area have been recently introduced as predictors of shock success, but their predictivity for shock success with low energy level is not known. Purpose: To assess whether amplitude spectral area (AMSA) of VF is able to predict the efficacy of low energy level defibrillation in out-of-hospital cardiac arrest (OHCA) patients. Methods: All the OHCAs with at least one shockable rhythm that occurred from January 2015 to December 2020 were considered. AMSA values were calculated by retrospectively analyzing the data collected by the Corpuls 3 monitors/defibrillators and by using a 2-second-pre-shock ECG interval. Results: Among 4619 OHCAs, resuscitation was attempted in 2982 (64%) and at least one shock was delivered in 697 (15%). AMSA values and defibrillation energy were available for 791 shocks, of which 45% received shock at low energy (>150J) and 55% at high energy (>150J). The rate of efficacy between the two groups was similar (44% vs 38%, p=0.102). However, in patients efficaciously treated with shock at low energy, AMSA was higher compared to those treated with shock at high energy [13.2 mV Hz (IQR 10.2–17) vs 10.8 mV Hz (IQR 8–13.8), p<0.001]. Moreover, AMSA values were significantly different when comparing ineffective shock at low energy with effective shock at high energy [6.6 mV Hz (IQR 4.6–10) vs 10.8 mV Hz (IQR 8.1–13.8), p<0.001] and similar when comparing ineffective shock at low and high energy [6.6 mV Hz (IQR 4.6–10) vs 6.3 mV Hz (IQR 4.5–8.7), p=0.21]. By dividing AMSA values into three tertiles, the rate of shock success at low energy was statistically different: [T1 (0.7–6.2 mV Hz) 4.2%; T2 (6.2–10.8 mV Hz) 13%; T3 (10.8–63.2 mV Hz) 42%; Chi-squared p<0.001 and p for trend <0.001]. After correction for age, sex, amiodarone use and call to shock time, AMSA values corresponding to the third and second tertile were associated with higher probability of shock success at low energy compared to the lowest tertile [T3 OR 15 (95% CI 7–30), p<0.001; T2 OR 3 (95% CI 1–7), p=0.002]. Conclusion: Ventricular fibrillation amplitude spectral area is a predictor of shock success at a low energy level. This could be useful to optimize both time and dose-energy to patients, yielding the highest chance for successful defibrillation while reducing the number of futile shocks and thus limiting the total current myocardial energy as well as CPR interruptions. Funding Acknowledgement: Type of funding sources: None.